Evaluating associations between metabolic health, obesity and depressive symptoms: a prospective analysis of data from the English Longitudinal Study of Ageing (ELSA) with a 2‑year follow‑up. Issue 12 (28th December 2018) - Slater, Natasha; Rowley, Charlotte; Venables, Rebecca Hayley; White, Simon; Frisher, Martin
Abstract : Objectives: Conflicting results have been reported when the associations between metabolic health, obesity and depression were examined previously. The primary aim of this study was to determine whether metabolic health or obesity are independently associated with depressive symptoms, among a representative sample of older people living in England. Independent associations between covariates and depression were also examined. Design: Prospective study with a 2-year follow-up. Setting: The English Longitudinal Study of Ageing Wave 6 (2012–2013) and Wave 7 (2014–2015). Participants: 6804 participants aged older than 50 years. Data Analysis: Multivariate models were used to determine whether metabolic health or obesity are independently associated with depressive symptoms at 2-year follow-up. Unadjusted and adjusted ORs with corresponding 95% CI were calculated; the adjusted ORs took account of baseline depression, gender, age, wealth, obesity and poor metabolic health. Results: Before adjusting for covariates, poor metabolic health was associated with depressive symptoms at 2-year follow-up (OR 1.24; 95% CI, 1.07 to 1.44, p<0.01). After adjusting for covariates, the association was no longer statistically significant (OR 1.17; 95% CI, 0.99 to 1.38, p=0.07). Similarly, obesity was associated with depressive symptoms at 2-year follow-up before adjusting for covariates (OR 1.54; 95% CI, 1.33 to 1.79, p<0.01). However, after adjusting for covariates the association between obesity and depressive symptoms at 2-year follow-up became statistically insignificant (OR 1.19; 95% CI, 1.00 to 1.41, p=0.06). The strongest predictors for future depression were baseline depression (OR 10.59; 95% CI, 8.90 to 12.53, p<0.01) and lower wealth (OR 3.23; 95% CI, 2.44 to 4.35, p<0.01). Conclusion: Neither poor metabolic health nor obesity were associated with a risk of depressive symptoms at 2-year follow-up, after adjusting for covariates. As wealth inequalities continue to rise across England, the risk of depressive symptoms at 2-year follow-up is likely to be elevated in individuals living in the lower wealth quintiles.